Andong Agimat the mystery of the talisman : a graphic novel - Arre, Arnold (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2022)
In this spellbinding action-adventure from Arnold Arre—the great master of the graphic novel, the age-old divide between good and evil widens. Catch a glimpse of a Manila privy to only a few of the supernatural and magically inclined, while following a superhero born and raised by its streets in The World of Andong Agimat.